Effectiveness of Agricultural Extension Wildlife Mitigation Strategies on Human-Wildlife Conflict Among Small-Scale Maize Farmers in Laikipia County, Kenya - Ronald Orare Nyamwamu; Justus Moturi Ombati (Journal of International Agricultural and Extension Education, 2018)
Agriculture is critical in the achievement of food security, employment of creation opportunities, steering economic growth, and also a source of raw materials for agricultural industries in many Sub-Saharan countries. However, farmers face various challenges which negatively affect farm productivity and production. Human-wildlife conflict is one of the most pressing challenges that smallholder maize farmers experience in some parts of Kenya. It arises from either people’s encroachment on wildlife habitats or the movement of wildlife from their natural habitat into neighboring farmland. Small-scale farmers use various agricultural extension strategies to mitigate the conflict. However, the effectiveness of the agricultural extension mitigation strategies adopted by smallholder maize farmers in Laikipia County had not been investigated and information on the same was inadequate and poorly documented. This study sought to determine the effectiveness of the agricultural extension wildlife conflict mitigation strategies adopted by smallholder maize farmers in Laikipia County. Whereas a document review guide was used to collect secondary data, semi-structured questionnaires were used to collect primary data from maize farmers and extension agents. Descriptive statistics were used to analyze primary data. It was established that crop damage was very severe, even up to 70% per cropping season although farmers used mitigation strategies such growing of unpalatable plants, live fences, hairy crops, and digging trenches. This study concluded that the Agricultural Extension Mitigation Strategies used were not effective. It was recommended concerted efforts between stakeholders in the conflict to realize the benefits of synergies so as to stem crop damage and give small-scale farmers a chance to be food secure.
Keywords: human-wildlife conflict; maize; mitigation strategies; smallholder farmers; Kenya